Pembelajaran Pencemaran Lingkungan Menggunakan Model Discovery Learning berbasis STEAM terhadap Keterampilan Berpikir Kreatif Siswa Kelas X MIPA - Rd Fauzan Rachmat Supriaman (Edukhasi: Jurnal Inovasi Pendidikan, 2023)
Creative thinking skill is the one of high orther thinking skill that needed to create development for education in Indonesia at 21st century. An initial study from one of senior high schools in Ciamis district showed that students' creative thinking skills tended to be low because the model that used for learning was not appropriate. The purpose of this study was to determine the effect of Discovery Learning model-based STEAM on students' creative thinking skills in the environmental pollution submaterial. This research was conducted using a Quasi Experiment with a Purposive Sampling technique for two classes that were used as subjects and research samples consisting of control and experimental classes. Pretest and posttest which contain indicators of creative thinking are given to students to measure the effect which is tested using prerequisite tests and hypothesis testing. The results of the prerequisite test show that the post-test data are normally distributed and not homogeneous. The hypothesis test gave the result that there was an influence on students' creative thinking skills after using the Discovery Learning model based STEAM in the submaterial of environmental pollution.